Edge effect in litter and nutrient stock in a native forest fragment in Pampa Biome-RS - Vogel, Hamilton Luiz Munari; Lorentz, Leandro Homrich; Azevedo, Jauris Vinícius Sampaio; Rott, Luis Augusto Goi; Motta, Málaga Soutto Mayor da (Revista Ecologia e Nutrição Florestal - ENFLO, 2014)
In the region of the Pampa biome, today there are few areas of remaining native forests, forming fragments with different degrees of disturbance, with few studies already carried out in nutrient cycling. The present work has as main objective quantify of accumulated litter and nutrients contained therein, the four seasons, the edge and inside in a fragment of a Seasonal Subtropical Forest in a backslope within the municipality of Vila Nova do Sul. Four plots were marked on the fragment in the sense inner edge, in the following positions: 0-10 m (10 samples), 10-20 m (10 samples), 20-50 m (15 samples) and 50-100 m (25 samples) total of 60 samples of litter. The samples were formed by the litter on the ground, collected with a wooden frame (25 cm x 25 cm), during autumn, winter and spring of 2011 and summer of 2012. There was a greater accumulation of litter on the ground in the forest interior than in relation to the edge, for all seasons. In the springtime there was more litter production, followed by winter. The stock of nutrients in the litter layer increases with increasing distance from the edge of the forest fragment in all seasons. The largest nutrient stocks were deposited in the springtime (mainly Ca), followed by winter, the lowest stock of nutrients occurred in the summer.